Genetically engineered microorganisms for the detection of explosives’ residues - Shemer, Benjamin; Palevsky, Noa; Yagur-Kroll, Sharon; Belkin, Shimshon (Frontiers in Microbiology, 2015)
The manufacture and use of explosives throughout the past century has resulted in the extensive pollution of soils and groundwater, and the widespread interment of landmines imposes a major humanitarian risk and prevents civil development of large areas. As most current landmine detection technologies require actual presence at the surveyed areas, thus posing a significant risk to personnel, diverse research efforts are aimed at the development of remote detection solutions. One possible means proposed to fulfill this objective is the use of microbial bioreporters: genetically engineered microorganisms “tailored” to generate an optical signal in the presence of explosives’ vapors. The use of such sensor bacteria will allow to pinpoint the locations of explosive devices in a minefield. While no study has yet resulted in a commercially operational system, significant progress has been made in the design and construction of explosives-sensing bacterial strains. In this article we review the attempts to construct microbial bioreporters for the detection of explosives, and analyze the steps that need to be undertaken for this strategy to be applicable for landmine detection.